Keeping memories cinema and archiving in the Asia-Pacific - Deocampo, Nick (Bughaw, 2022)
This book brings together film scholars, archivists, film artists, academics, media practitioners, historians, and cultural advocates to share their thoughts that touch the heart of our Asian film heritage. In four themes, the sections in this anthology deal with topics such as Archives and Memory, Archives and National Identity, Archives and the Asia-Pacific, and Archives and Cinema History. Merely over a century old, films produced in the region are already irredeemably lost. Works made by filmmakers like Yasujiro Ozu, King Hu, Lino Brocka, Woon-kyu Na, and Ji-ming He, to name a few, have disappeared through natural causes, technological obsolescence, and human neglect. How much has the loss of their films impoverished our knowledge of Asian cinema? What future awaits those that still survive of the analogue and the digital native productions? In addressing these themes, the book significantly contributes to the deepening knowledge not only about archiving in the region but also about the film culture wrapping around the motion pictures, which archives seek to preserve.